Characteristics of fasting users among internal medicine patients in Germany. Issue 1 (April 2018) - Lauche, Romy; Wardle, Jon; Ostermann, Thomas; Adams, Jon; Langhorst, Jost; Dobos, Gustav; Michalsen, Andreas; Cramer, Holger
Abstract: Aim: The aim of this cross-sectional analysis was to identify sociodemographic, and health related predictors for fasting use among patients of a large integrative internal medicine ward. Methods: A cross-sectional analysis was conducted among patients being referred to a hospital for internal and integrative medicine. Patients' ever-use of fasting for their primary medical complaint and their perceptions of benefit and harm were assessed. The potential predictors of fasting use included sociodemographic characteristics, health behaviour, internal medicine diagnosis, health, satisfaction with health, and health locus of control; and they were analysed using multiple logistic regression analysis. Results: Of 2144 respondents, 15.8% reported having used fasting, with 61.2% reporting perceived benefits and 3.9% harms due to use. Fasting use was positively associated with higher education, being diagnosed with osteoarthritis or fibromyalgia and regular fast food use, while patients with inflammatory bowel diseases, smokers, alcohol abstinent people and those with a high external social health locus of control were less likely to use fasting. A good health status and high internal locus of control were positively associated with the perception of fasting as helpful, while part-time employment, being diagnosed with inflammatory bowel diseases and being alcohol abstinent were negatively associated with perceived helpfulness. Conclusion: There is significant use of therapeutic fasting by integrative medicine patients in Germany, with high self-reported benefit and low self-reported harms. Use of fasting by patients was not related to evidence of efficacy of fasting for their condition, with other factors being more predictive of fasting use.